2021
DOI: 10.1007/s10854-021-05989-1
|View full text |Cite
|
Sign up to set email alerts
|

A robust 3D self-powered photoelectrochemical type photodetector based on MoSe2 nanoflower

Abstract: Molybdenum selenide (MoSe 2 ) has been extensively studied in recent years due to its strong absorption for sunlight and unique band structure. Herein, a self-assembly three-dimensional (3D) MoSe 2 nano owers were prepared by a two-step process. Signi cantly, the photodetection device based on MoSe 2 nano owers exhibited a maximum responsivity about 12.39mA/W and a rapid photo-response time about 0.15s at 0V bias under simulated sunlight exposure bene ting from its large speci c surface area and unique morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The bandgap values of MoSe 2 and WSe 2 NSs are 1.55 eV and 1.50 eV, respectively, which is higher than their bulk counterpart as reported in the literature. 53 , 54 This difference in bandgap suggests that the bulk MoSe 2 and WSe 2 are reduced to few-layer-thick NSs. 52 …”
Section: Resultsmentioning
confidence: 99%
“…The bandgap values of MoSe 2 and WSe 2 NSs are 1.55 eV and 1.50 eV, respectively, which is higher than their bulk counterpart as reported in the literature. 53 , 54 This difference in bandgap suggests that the bulk MoSe 2 and WSe 2 are reduced to few-layer-thick NSs. 52 …”
Section: Resultsmentioning
confidence: 99%
“…In 2019, Xie et al [171] demonstrated that 2D non-layered Te NSs displayed excellent PEC behavior from the UV to the visible region in association with excellent PEC stability. In 2021, Qi et al [186] successfully fabricated 3D MoSe 2 nanoflowers by hydrothermal and CVD methods displayed a maximum responsivity (R ph ) about 12.39 µA W −1 and a fast photoresponse time of ≈0.15 s at 0 V under SL due to relatively large specific surface area and complex morphologic structure, as well as outstanding photoresponse stability for two weeks. Apart from these structural designs, in 2021, Zhang et al [165] used PbSe NCs fabricated by a facile LPE approach as active materials to construct high-performance PEC-type photodetectors.…”
Section: Pec Photodetectionmentioning
confidence: 99%
“…Considerable effort has been made to study the H-phase MoS 2 in the fields of electronics, photonics, and photo-catalytic chemistry [21]. Molybdenum selenide (MoSe 2 ) has also been extensively researched due to its strong absorption of sunlight and unique band structure while molybdenum telluride (MoTe 2 ) is gaining interest in electronic and optoelectronic devices [22]. These 2D materials show interesting properties that can be harnessed to remove environmental pollutants by catalysis and adsorption.…”
Section: Introductionmentioning
confidence: 99%